Photocatalytic hydrogen evolution over β-iron silicide under infrared-light irradiation. Issue 14 (13th January 2015) - Yoshimizu, Masaharu; Kobayashi, Ryoya; Saegusa, Makoto; Takashima, Toshihiro; Funakubo, Hiroshi; Akiyama, Kensuke; Matsumoto, Yoshihisa; Irie, Hiroshi
Abstract : We investigated the ability of β-FeSi2 (0.80 eV) to serve as a hydrogen (H2 )-evolution photocatalyst, sensitive to infrared light (>1300 nm). Abstract : We investigated the ability of β-iron silicide (β-FeSi2 ) to serve as a hydrogen (H2 )-evolution photocatalyst due to the potential of its conduction band bottom, which may allow thermodynamically favorable H2 evolution in spite of its small band-gap of 0.80 eV. β-FeSi2 had an apparent quantum efficiency for H2 evolution of ∼24% up to 950 nm (near infrared light), in the presence of the dithionic acid ion (S2 O6 2− ) as a sacrificial agent. It was also sensitive to infrared light (>1300 nm) for H2 evolution.